2018
DOI: 10.1016/j.beha.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of follicular lymphoma

Abstract: The hallmark t(14;18)(q32;q21) in follicular lymphoma (FL) results in constitutive overexpression of the BCL2 protein, allowing B cells to abrogate the default germinal center apoptotic program. Most tumors are characterized by recurrent secondary genetic alterations including genomic gains, losses, and mutations, some providing a growth advantage, including alterations in MLL2, EPHA7, TNFRSF14, and EZH2. The sequence in which these events occur and how they contribute to progression and ultimately to transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 168 publications
3
27
0
Order By: Relevance
“…For example, STAT3 is considered a key driver gene of large granular lymphocyte leukemia (LGL), and STAT3 mutations have been found in both NK cell -type and T celltype LGL [37]. Another study detected KMT2D mutations in patients with a variety of lymphoproliferative diseases [38][39][40], although the specific mechanism of action is still unclear. The other previously mentioned mutant genes have also been reported to be associated with various types of lymphoproliferative diseases or tumors [41][42][43][44][45][46], but no studies have detected mutations in these aforementioned genes in patients with HVLPD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, STAT3 is considered a key driver gene of large granular lymphocyte leukemia (LGL), and STAT3 mutations have been found in both NK cell -type and T celltype LGL [37]. Another study detected KMT2D mutations in patients with a variety of lymphoproliferative diseases [38][39][40], although the specific mechanism of action is still unclear. The other previously mentioned mutant genes have also been reported to be associated with various types of lymphoproliferative diseases or tumors [41][42][43][44][45][46], but no studies have detected mutations in these aforementioned genes in patients with HVLPD.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of follicular lymphoma (FL), the most common indolent B-cell non-Hodgkin lymphoma characterized by the presence of t (14;18) and BCL-2 overexpression, is thought to be the result of a close collaboration between recurrent somatic mutations and a permissive microenvironment. 1,2 FL tumor cells are dependent on their microenvironment for proliferation and survival, remaining dependent on signals through the B-cell receptor (BCR). 3 In this context, 2 populations present in the tumor niche are fundamental: follicular dendritic cells (FDCs) and dendritic cellspecific intercellular adhesion molecule-3-grabbing nonintegrinexpressing macrophages (Mf).…”
Section: Introductionmentioning
confidence: 99%
“…FL can be classified according to the WHO into grade I-III categories based on histological features that correlate with clinical outcome. Several large studies have identified numerous recurrent mutations affecting the B-cell receptor signaling and differentiation, cell cycle regulation, derangements of epigenetic modification and immune evasion that can be linked to clinical progression of the disease [22][23][24][25], however the mechanism of clonal evolution is still a matter of debate [26,27]. The IgV H somatic hypermutation based spatial evolution of follicular lymphoma have been demonstrated previously [28,29].…”
Section: Discussionmentioning
confidence: 99%